Geosystem Services of Erratic Boulders in Selected Regions of Central Poland - Maria Górska-Zabielska; Anna Łubek (Resources)
Scandinavian erratic boulders in central Poland represent a significant element of the region’s geodiversity, fulfilling important natural, scientific, and cultural functions. As objects of high perceptual value, they integrate into the landscape and provide a wide range of geosystem services. The main objectives of research conducted in two areas of the Małopolska Upland are to determine the concentration of these boulders and identify the geosystem benefits they offer, with particular emphasis on lichen species inhabiting their surfaces. Research has confirmed the currently limited use of geosystem services provided by the 25 erratic boulders studied. However, this may change with growing ecological awareness among local communities, enabling a deeper appreciation of inanimate nature. Erratic boulders have the potential to attract geotourists and thus support economic development (by improving the residents’ quality of life), but this potential requires broader promotion. Although the Central Register of Geosites of Poland is an appropriate platform for their registration, none of the analysed boulders have yet been included. The research findings are also partly directed at local government units to help them recognise the value of erratic boulders for sustainable development, in line with existing legal frameworks and development strategies. The detailed characterisation of 25 boulders may inspire broader initiatives and foster knowledge transfer to support regional development through geotourism. The ability to identify the ecosystem benefits provided by erratic boulders is essential for maintaining ecological balance and sustaining natural processes. However, there is growing evidence of the systematic disappearance of erratic boulders from the landscape, which disrupts geosystem balance and leads to further environmental degradation, negatively affecting human well-being. In light of the lack of effective nature protection measures in the study area, it is proposed that some of these boulders be designated as geological protected features. Such a conservation approach could help maintain ecological balance in the designated area.